2015
DOI: 10.1016/j.visres.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection and recognition of angular frequency patterns

Abstract: Previous research has extensively explored visual encoding of smoothly curved, closed contours described by sinusoidal variation of pattern radius as a function of polar angle (RF patterns). Although the contours of many biologically significant objects are curved, we also confront shapes with a more jagged and angular appearance. To study these, we introduce here a novel class of visual stimuli that deform smoothly from a circle to an equilateral polygon with N sides (AF patterns). Threshold measurements reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
2
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(131 citation statements)
references
References 25 publications
7
120
2
2
Order By: Relevance
“…Although our study did not test other stimuli related to local-global pattern processing, previous psychophysical studies have shown similar effects on localglobal pattern processing using different stimuli (e.g., radial frequency patterns; Habak, Wilkinson, Zakher, & Wilson, 2004;Wilkinson, Wilson, & Habak, 1998). Brain imaging studies on local-global tasks using other types of stimuli (Navon figures (Navon, 1977), parametrically degraded objects, etc.)…”
Section: Discussionmentioning
confidence: 82%
“…Although our study did not test other stimuli related to local-global pattern processing, previous psychophysical studies have shown similar effects on localglobal pattern processing using different stimuli (e.g., radial frequency patterns; Habak, Wilkinson, Zakher, & Wilson, 2004;Wilkinson, Wilson, & Habak, 1998). Brain imaging studies on local-global tasks using other types of stimuli (Navon figures (Navon, 1977), parametrically degraded objects, etc.)…”
Section: Discussionmentioning
confidence: 82%
“…Perceiving visual form initially requires accurate encoding of local orientation information, and then integrating separate features into global forms and segregating them from their backgrounds [42,67,69]. RF pattern discrimination is thought to tap intermediate stages of visual form processing [41], where separate features are pooled into global forms.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate perception of visual form, we measured the ability to discriminate radial frequency (RF) patterns of varying modulations in amplitude from a perfect circle. RF patterns, first created by Wilkinson et al [67], are a family of smooth closed shapes that differ from each other and each from a perfect circle in a well-defined way: different patterns can be created by modulating the amplitude (affecting the sharpness or depth of the lobe), radial frequency (the number of lobes) and the orientation (the direction of the lobe). To investigate the link between the abilities to perceive visual form and facial expressions of emotion in PD, we correlated measures of discriminating RF3 patterns from perfect circles with measures of discriminating graded intensities of angry from neutral expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al (2010a) constructed a new visual search task using radial frequency (RF) patterns (see Section 2). RF patterns are created by deforming a circle through varying its radius sinusoidally as a function of polar angle, with the number of modulation cycles required to complete one revolution corresponding to the RF number (Wilkinson, Wilson, & Habak, 1998). These patterns were chosen because, like the simple target shape in the EFT, they are also closed contours, but they can be adjusted to evoke welldefined global or local closed-contour processing mechanisms (Bell & Badcock, 2009;Hess, Wang, & Dakin, 1999;Loffler, Wilson, & Wilkinson, 2003).…”
Section: Introductionmentioning
confidence: 99%